2006
DOI: 10.1128/aac.50.4.1393-1401.2006
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorothioate Oligonucleotides Inhibit Human Immunodeficiency Virus Type 1 Fusion by Blocking gp41 Core Formation

Abstract: Several studies have shown that phosphorothioate oligodeoxynucleotides (PS-ONs) have a sequence-independent antiviral activity against human immunodeficiency virus type 1 (HIV-1). It has also been suggested that PS-ONs inhibit HIV-1 by acting as attachment inhibitors that bind to the V3 loop of gp120 and prevent the gp120-CD4 interaction. Here we show that PS-ONs (and their fully 2-O-methylated derivatives) are potent inhibitors of HIV-1-mediated membrane fusion and HIV-1 replication in a size-dependent, phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 43 publications
3
102
1
Order By: Relevance
“…In the case of viral entry, NAP-protein interactions destroy the ability of amphipathic protein domains present in viral fusion glycoproteins to interact with each other, a process known to be important in catalyzing the entry of many enveloped viruses into their host cells (15). In HIV-1 and LCMV, the interaction of NAPs with viral fusion proteins is consistent with their ability to block viral entry, and they have little or no postentry antiviral activity (13,14).…”
Section: Uck Hepatitis B Virus (Dhbv) In Its Natural Host the Pekimentioning
confidence: 96%
See 1 more Smart Citation
“…In the case of viral entry, NAP-protein interactions destroy the ability of amphipathic protein domains present in viral fusion glycoproteins to interact with each other, a process known to be important in catalyzing the entry of many enveloped viruses into their host cells (15). In HIV-1 and LCMV, the interaction of NAPs with viral fusion proteins is consistent with their ability to block viral entry, and they have little or no postentry antiviral activity (13,14).…”
Section: Uck Hepatitis B Virus (Dhbv) In Its Natural Host the Pekimentioning
confidence: 96%
“…For example, NAPs have been shown to interact with prion proteins (12) and type 1 viral fusion glycoproteins in both human immunodeficiency virus type 1 (HIV-1) and lymphocytic choriomeningitis virus (LCMV) (13,14). In the case of viral entry, NAP-protein interactions destroy the ability of amphipathic protein domains present in viral fusion glycoproteins to interact with each other, a process known to be important in catalyzing the entry of many enveloped viruses into their host cells (15).…”
Section: Uck Hepatitis B Virus (Dhbv) In Its Natural Host the Pekimentioning
confidence: 99%
“…binding inhibition. This phenomenon could be extended to the inhibition of virus entry, as it has been recently shown that human cytomegalovirus, hepatitis C virus, and HIV entry are blocked by phosphorothioate-modified ODNs, regardless of CpG motifs (33)(34)(35)(36). One could therefore take advantage of this to design antiviral vaccines that target virus entry.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the tetrameric G-quartet structure and the sulfur-containing backbone are believed to be involved in binding to V3, followed by the inhibition of virus-to-cell and cell-to-cell infections. Another study showed that P = S ONs interact with a peptide derived from the N-terminal heptad repeat region of gp41, blocking gp41 sixhelix bundle formation (Vaillant et al, 2006). Recently, a short 14-mer P = S 2′ deoxyribose backbone was demonstrated to enhance anti-HIV-1 activity by blocking Toll-like receptor 7 (TLR7) and TLR9, thus inhibiting the initial spread of HIV-1 after infection (Fraietta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These suggested mechanisms include blocking of viral adsorption (Luganini et al, 2008;Wyatt et al, 1994) and/or inhibition of HIV-1-specific enzymes, such as reverse transcriptase (Marshall and Caruthers, 1993;Marshall et al, 1992) or integrase (Jing and Hogan, 1998;Jing et al, 2000). P = S oligodeoxycytidine [poly (SdC) 28 ] interacts specifically with the positively-charged V3 loop of HIV-1 gp120 (Vaillant et al, 2006), possibly resulting in the inhibition of HIV-1 replication. It was also reported that T2G4T2 (5-TTGGGGTT-3; ISIS-5320), a P = S ON identified as an HIV-1 inhibitor, forms a tetrameric G-quartet structure and binds to the cationic V3 loop region of the gp120 viral envelope glycoprotein , as does poly(SdC) 28 .…”
Section: Introductionmentioning
confidence: 99%